The association between glutathione S-transferase gene polymorphisms and pancreatic cancer in a central European Slavonic population - Vrána, David; Pikhart, Hynek; Mohelníková-Duchoňová, Beatrice; Holcátová, Ivana; Strnad, Robin; Slámová, Alena; Schejbalová, Miriam; Ryska, Miroslav; Šůsová, Simona; Souček, Pavel (Mutation research, 2009)
In the first case-control study on pancreatic cancer conducted on 253 cases and 403 controls in the Czech Republic we observed that the GSTP1-codon 105 Val variant allele and the GSTT1-null genotype were associated with an elevated risk for pancreatic cancer (OR = 1.38; 95%CI = 0.96-1.97 and OR = 1.56; 95%CI = 0.93-2.61, respectively). Combination of GSTT1-null and GSTP1-codon 105 Val variants further increased the risk for pancreatic cancer (OR = 2.50; 95%CI = 1.20-5.20). In conclusion, this study suggests population-specific associations of polymorphisms in key biotransformation genes with elevated risk for pancreatic cancer.
Keywords: glutathiontransferasa; Male; Genetic Predisposition to Disease; Glutathione S-Transferase pi; Glutathione Transferase; glutathion-S-transferasa fí; Česká republika; Adult; Aged; dospělí; mužské pohlaví; senioři; jednonukleotidový polymorfismus; Pancreatic Neoplasms; Czech Republic; senioři nad 80 let; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; adenokarcinom; Humans; nádory slinivky břišní; Aged, 80 and over; DNA; Adenocarcinoma; Female; lidé středního věku; genetická predispozice k nemoci; Middle Aged